PENGARUH TERPAAN PROMOSI PENJUALAN “HARI BANGGA BUATAN INDONESIA” DAN CITRA MEREK “ERIGO” TERHADAP MINAT BELI - Dinda Salsabella, Anisa; Sunarto, Sunarto; Luqman, Yanuar (Interaksi Online, 2024)
Through the "Hari Bangga Buatan Indonesia" program, the government projects online shopping transactions on BBI Day to exceed IDR 11.6 trillion. However, based on NielsenIQ research, the sales contribution for local products was recorded at only IDR 8.5 trillion out of total transactions of IDR 18.1 trillion in 2021. Even though the implementation of national online shopping which coincides with "Hari Bangga Buatan Indonesia", it was held over a longer period, namely for nine days, compared to the previous year which was only held for two days (11 - 12 December). This research aims to determine the effect of exposure to the sales promotion "Hari Bangga Buatan Indonesia" and the brand image of "Erigo" on purchasing interest. The theory used in this research is the Elaboration Likelihood Model. The number of samples in this study was 100 people aged 18-28 years who lived in Indonesia and were aware of the sales promotion for Proudly Made in Indonesia Day. The sampling technique in this research is non-probability sampling. The results of the research show that there is an influence of exposure to the sales promotion "Proudly Made in Indonesia Day" on purchasing interest with a significance value of 0.000 and an influence size of 15.64%. Second, there is an influence of the "Erigo" brand image on purchase intention with a significance value of 0.000 and an influence size of 44.58%. Third, exposure to the sales promotion "Proudly Made in Indonesia Day" and the brand image "Erigo" simultaneously (together) had a significant positive effect on purchase intention with an influence size of 60.2%.